2019
DOI: 10.1002/kin.21273
|View full text |Cite
|
Sign up to set email alerts
|

Deep eutectic solvent as an operative media on structure‐reactivity relationships

Abstract: Deep eutectic solvents seem to be environmentally friendly solvents, particularly because they are prepared easily and have very low‐vapor pressures under ambient conditions. They are suitable candidates as green solvents for reaction media with special properties. To present this behavior, substitution reactions of some para‐ and meta‐substituted anilines with 1‐fluoro‐2,4‐dinitrobenzene have been spectrophotometrically investigated in varying mole fractions of ethaline as a deep eutectic solvent in dimethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…These {glyceline+DMSO} mixtures, which are stable over the entire composition range for temperatures T ≥ 293.15 K, are of practical interest due to their significantly lower viscosity compared to neat glyceline. Recently, DESs mixed with DMSO have been considered as operative media for substitution reactions of para- and meta-substituted anilines with 1-fluoro-2,4-dinitrobenzene. , The employed DESs were 1:2 ChCl/ethylene glycol, usually called ethaline, , and glyceline . The analysis of the solvent effect on the reaction kinetics showed that the reactants and intermediate products are preferentially solvated by DES components and DMSO, respectively, which can be used as a factor of controlling the reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…These {glyceline+DMSO} mixtures, which are stable over the entire composition range for temperatures T ≥ 293.15 K, are of practical interest due to their significantly lower viscosity compared to neat glyceline. Recently, DESs mixed with DMSO have been considered as operative media for substitution reactions of para- and meta-substituted anilines with 1-fluoro-2,4-dinitrobenzene. , The employed DESs were 1:2 ChCl/ethylene glycol, usually called ethaline, , and glyceline . The analysis of the solvent effect on the reaction kinetics showed that the reactants and intermediate products are preferentially solvated by DES components and DMSO, respectively, which can be used as a factor of controlling the reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…2 (d, F-C-C 2,4-Dinitrofluorobenzene 1 (200 mg, 1.1 mmol) in EtOH (15 mL) was mixed with aniline (200 mg, 2.2 mmol) for 3 h at room temperature. 25 The precipitate was filtered and air dried to give the title compound (130 mg, 46 %) as orange/ red crystals, m.p. 158-159 °C (from dichloromethane:light petroleum ether).…”
Section: -Nitro-5-fluorophenyl-p-phenylenediamine 11mentioning
confidence: 99%
“…Let us start by considering a homologous reaction series that follows either the Hammett or the Taft equation irrespectively of temperature (within a certain range). In the hypothetical case chosen as an example, the reaction constant (slope of the LFER-type plot) is negative (  or *  < 0), corresponding to a favorable effect of the electron-donating substituents [55,56], whereas a positive value (  or *  > 0) would correspond to a favorable effect of the electron-withdrawing substituents [57,58].…”
Section: Lfer-type Relationships and Kinetic Compensation Effectmentioning
confidence: 99%